PENGARUH HARGA DAN KUALITAS JASA JNE EKSPRESS TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABLE INTERVENING (Studi Kasus JNE Cabang Kota Semarang) - Vito Alfianno; Ngatno Ngatno (Universitas Diponegoro, 2017)
Price can affect the service quality while the service is directly propotional then the consumer will experience satisfaction with the services provided, if there has arisen satisfaction then the consumer can be loyal to the company. In this logistic delivery service JNE Express pay attention to price and quality of services so that consumers can feel satisfaction after using JNE services with expectation to make loyal consumers with JNE Express.This study intend to determine the effect of price towards satisfaction, quality of services towards satisfaction, price and quality of services towards satisfaction, price towards loyalty, quality of services towards loyalty, price and quality of services towards loyalty, price towards loyalty through satisfaction, and quality of services towards loyalty through satisfaction. In this study the population are the consumers of JNE Semarang City by taking 100 samples. The type of this research is explanatory research with quantitative approach. The analysis technique using correlation test, determination test, simple regression test, signification test, sobel test, mediation test using SPSS version 16 application.The result of this research indicate that the price has a significant effect towards satisfaction, quality of services has significant effect towards satisfaction, price and quality of services have effect towards satisfaction, satisfaction has effect towards loyalty, price has effect towards loyalty, quality of services has effect towards loyalty, price has effect towards loyalty through satisfaction partial mediation, quality of services has effect towards loyalty through satisfaction with partial mediation. Each hypothesis test has a significant 0.00.As a suggestion JNE Semarang should maintain the price and quality of services level so that consumers will be satisfied with the service, so that consumers will loyal with JNE Semarang services.